1985
DOI: 10.1021/bi00340a033
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetimes of carbocyanine lipid analogs in phospholipid bilayers

Abstract: The fluorescence lifetimes for the 1,1'-dialkyl-3,3,3',3'-tetramethylindocarbocyanine (CNdiI) dyes (N = 12, 18, and 22) in a variety of lipid bilayer membranes were measured. Effects of bilayer physical state, probe chain length, probe concentration, charge, lipid head group, and cholesterol concentration were examined. Even in single-phase membranes these probes did not exhibit single-exponential decays. Rather, the data were fit by biexponential decays with lifetimes of approximately 0.3-0.4 and approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
48
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 34 publications
14
48
0
Order By: Relevance
“…2). From our solution results, model membrane results and literature, 55 we concluded that second lifetime component was more strongly affected by viscosity than the first component. Thus, we focused on the shear-induced changes in the longer exponent, for which values were obtained by tail fitting the portion of the histogram bin where first exponential and IRF are not relevant, i.e.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…2). From our solution results, model membrane results and literature, 55 we concluded that second lifetime component was more strongly affected by viscosity than the first component. Thus, we focused on the shear-induced changes in the longer exponent, for which values were obtained by tail fitting the portion of the histogram bin where first exponential and IRF are not relevant, i.e.…”
Section: Resultssupporting
confidence: 50%
“…34 The photophysics (e.g. fluorescence lifetime, quantum yield) have been well characterized, 55 and because these dyes share identical chromophores and differ only by their chain lengths, they are useful in definitively assigning their unique photophysical properties to different membrane domains. For most other “raft” associated dyes there is no structurally equivalent counter stain to probe non-raft regions.…”
Section: Introductionmentioning
confidence: 99%
“…In each solvent, fluorescence lifetimes were best fit using biexponential decays [Eq. (12)], consistent with earlier results 41 for DiI. Each value reported in Table 3 42 Using a single exponential to fit the lifetime curve, they obtained a value of 1.12 ns for the decay of DiD in ethanol.…”
Section: Fluorescence Lifetime Measurementssupporting
confidence: 87%
“…65,66 Moreover, Packard and Wolf have shown that fluorescence lifetime of DiI increases with an increase in order of the lipid acyl chains. 19 …”
Section: Resultsmentioning
confidence: 99%